Cannabinoid Receptors: Where They are and What They do - Mackie, K. (Journal of neuroendocrinology, 2008)
The endocannabinoid system consists of the endogenous cannabinoids (endocannabinoids), cannabinoid receptors and the enzymes that synthesise and degrade endocannabinoids. Many of the effects of cannabinoids and endocannabinoids are mediated by two G protein‐coupled receptors (GPCRs), CB1 and CB2, although additional receptors may be involved. CB1 receptors are present in very high levels in several brain regions and in lower amounts in a more widespread fashion. These receptors mediate many of the psychoactive effects of cannabinoids. CB2 receptors have a more restricted distribution, being found in a number of immune cells and in a few neurones. Both CB1 and CB2 couple primarily to inhibitory G proteins and are subject to the same pharmacological influences as other GPCRs. Thus, partial agonism, functional selectivity and inverse agonism all play important roles in determining the cellular response to specific cannabinoid receptor ligands.